2013
DOI: 10.1097/ta.0b013e3182a85f3a
|View full text |Cite
|
Sign up to set email alerts
|

Brain-type natriuretic peptide and right ventricular end-diastolic volume index measurements are imprecise estimates of circulating blood volume in critically ill subjects

Abstract: Diagnostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…BNP didn't appear to be a reliable marker of uid status in septic patients. Similar studies had also shown that BNP was not signi cantly associated with uid volume and uid responsiveness in patients with sepsis 24,25 . cTnI is the most sensitive and speci c marker of myocardial injury.…”
Section: Discussionmentioning
confidence: 68%
“…BNP didn't appear to be a reliable marker of uid status in septic patients. Similar studies had also shown that BNP was not signi cantly associated with uid volume and uid responsiveness in patients with sepsis 24,25 . cTnI is the most sensitive and speci c marker of myocardial injury.…”
Section: Discussionmentioning
confidence: 68%
“…BNP didn’t seem to be a reliable marker of fluid status in septic patients. Similar studies had also shown that BNP was not closely associated with fluid volume and fluid responsiveness in patients with sepsis[ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 83%
“…Elevated levels of BNP and NT‐proBNP have been associated with reduced ejection fraction and stroke volume, global tissue hypoxia, reduced cardiac index, sepsis induced myocardial dysfunction, prior cardiac dysfunction, diastolic left ventricular size and systolic as well as diastolic dysfunction . On the contrary, BNP has been found to be a poor predictor of volume status in critically ill patients, including patients with septic shock . Nevertheless, BNP levels have also been found to be elevated in patients with severe sepsis and septic shock in patients with normal left ventricular ejection fraction …”
Section: Resultsmentioning
confidence: 99%
“…29,32,36 On the contrary, BNP has been found to be a poor predictor of volume status in critically ill patients, including patients with septic shock. 53 Nevertheless, BNP levels have also been found to be elevated in patients with severe sepsis and septic shock in patients with normal left ventricular ejection fraction. 38 In addition, brain natriuretic peptides have been found to be significantly more increased in septic shock than in cardiogenic shock and have been used to distinguish between the two conditions.…”
Section: Brain Natriuretic Peptides Levels In Respect To Cardiac Fumentioning
confidence: 99%